QAnon, authoritarianism, and conspiracy within American alternative spiritual spaces - Conner, Christopher T. (Frontiers in Sociology, 2023)
Introduction QAnon, in the United States, has become something of household name due to its role in the January 6th insurrection, and because of the relatively high degree of media attention it has received. While such coverage has been useful in understanding this conspiracy movement, it has also painted a picture of QAnon that is incomplete. Methods Using a qualitative ethnographic approach I analyzed 1,000 hours of QAnon content produced by 100 QAnon influencers. I created a database of 4,104 images (tweets, screenshots, and other static forms of communication) and 122 videos. Results We found three separate cultural entry points not typically associated with the movement—Yoga and Wellness Groups, Neo-Shamanistic circles, and Psychics. By colonizing these spaces QAnon was able to embed itself, disguise its abrasive features, and go largely unnoticed by the general public. Discussion This study reminds us that authoritarianism can take root in a variety of spaces, and that within each of us lie potentially fascistic tendencies—even those seeking enlightenment, through alternative practices.